The (O)mission statements - Muchativugwa Hove (Communicare)
This paper interrogates the mission statements and strategic development plans of two universities in South Africa in order to unpack both the deficit and surplus messages embedded in them. One of the universities is located in a rural setting and was classified as formerly disadvantaged, while the other one was a formerly white and privileged university. This article is a qualitative study and employs a content and discursive analytic approach, together with McLaren’s (1994) typological framework on the four forms of multiculturalism in order to interrogate the mission statements and strategic development plans of the two universities in question. Both the mission statements and the strategic development plans are examined for the ways in which they discursively identify who is included and excluded from the realisation and attainment of the missions and development plans of the two universities studied. The article argues that specific discourse patterns emerge from the two universities’ mission statements and strategic development plans to the extent that either marginalising messages or promissory and empowering messages are conveyed inadvertently in the inscriptions. The article ultimately suggests that there is a need for a shift from a deficit discourse to looking critically and reflexively at current university practices and shortcomings in the use of discourse patterns to include or exclude significant agents in both the crafting and implementation of the principalities embedded in their mission statements and strategic development plans.